Recent Advances in the Mechanisms of Postoperative Neurocognitive Dysfunction: A Narrative Review - Tingting Wang; Xin Huang; Shujun Sun; Yafeng Wang; Linlin Han; Tao Zhang; Tianhao Zhang; Xiangdong Chen (Biomedicines)
Postoperative neurocognitive dysfunction (PND) is a prevalent and debilitating complication in elderly surgical patients, characterized by persistent cognitive decline that negatively affects recovery and quality of life. As the aging population grows, the rising number of elderly surgical patients has made PND an urgent clinical challenge. Despite increasing research efforts, the pathophysiological mechanisms underlying PND remain inadequately characterized, underscoring the need for a more integrated framework to guide targeted interventions. To better understand the molecular mechanisms and therapeutic targets of PND, this narrative review synthesized evidence from peer-reviewed studies, identified through comprehensive searches of PubMed, Embase, Cochrane Library, and Web of Science. Key findings highlight neuroinflammation, oxidative stress, mitochondrial dysfunction, neurotransmitter imbalances, microvascular changes, and white matter lesions as central to PND pathophysiology, with particular parallels to encephalocele- and sepsis-associated cognitive impairments. Among these, neuroinflammation, mediated by pathways such as the NLRP3 inflammasome and blood–brain barrier disruption, emerges as a pivotal driver, triggering cascades that exacerbate neuronal injury. Oxidative stress and mitochondrial dysfunction synergistically amplify these effects, while neurotransmitter imbalances and microvascular alterations, including white matter lesions, contribute to synaptic dysfunction and cognitive decline. Anesthetic agents modulate these interconnected pathways, exhibiting both protective and detrimental effects. Propofol and dexmedetomidine demonstrate neuroprotective properties by suppressing neuroinflammation and microglial activation, whereas inhalational anesthetics like sevoflurane intensify oxidative stress and inflammatory responses. Ketamine, with its anti-inflammatory potential, offers promise but requires further evaluation to determine its long-term safety and efficacy. By bridging molecular insights with clinical practice, this review highlights the critical role of personalized anesthetic strategies in mitigating PND and improving cognitive recovery in elderly surgical patients. It aims to inform future research and clinical decision-making to address this multifaceted challenge.